PENGELOLAAN ARSIP DALAM MENDUKUNG TERTIB ADMINISTRASI DI UNIVERSITAS DHARMA ANDALAS PADANG - Erdasti Husni; Dian Hirma (Jurnal Ekonomi dan Bisnis Dharma Andalas, 2019)
Based on pilot study, researcher found that all units in the Dharma Andalas University didn’t implement the methods of filling document’s classification or didn’t use any special method to save all documents yet, there were few problem’s phenomena are indicated in this matters, such as the unsystematic filing system, there was no officers who handled the management of the documents and also limited storages for filling the documents. The formulation of the problem from this research is to know how the functions of files’ management (planning, organizing, controlling and supervision) in order to support good administration at Dharma Andalas University. The purpose of this research are to explore and describes all function of files’ management (planning, organizing, controlling and supervision) to support good administration at Dharma Andalas University Padang. Source of data was collected from 20 (twenty) participants include the Head of Human Resource and the Head of Academic Bereau of Dharma Andalas University. Indepth interview, small grup discussion, observation are carried out as a data collection techniques to observed documents and standard operational procedure in compiled the documents. The analysis of this research are using qualitative method by analyzed primary data and secondary data which described the files’ management. Data analysis includes data reduction, data presentation and decision making. The results of this research was described that Files’ management includes planning, implementation, control and supervision, has not been run effectively and efficiently so that it cannot support good administration at Dharma Andalas University.